Kinetics of Fluorescein Sodium Salt /Polystyrene (FFS/PS) Composites by TG Technique - Dere, Aysegul (My University, 2019)
The fluorescein sodium salt (FSS) /polystyrene (PS) composites were prepared by powder metallurgy method (PM). The thermalbehavior of the composites was characterized by thermogravimetric analysis (TG) technique. It is observed that the compositesdecompose in two steps. The kinetic parameters (activation energy, frequency factor) and thermodynamic parameters (enthalpy $\\triangle$H#change, entropy change $\\triangle$S# and Gibbs free energy change $\\triangle$G#) were calculated from the TG curves. Eight g($\\alpha$) functions fordecomposition mechanism (DM) were used to evaluate the kinetic parameters and analysis of experimental results suggests that in thefirst decomposition step, the actual DM is D3 type which is the three-dimensional diffusion mechanism for the first decomposition stepof the composites. But, in the second decomposition step, it was observed that the decomposition mechanism is from one-dimensionaldiffusion (D1) to the random nucleation mechanism (F1).
Keywords: Nanobilim ve Nanoteknoloji; Termodinamik; Kimya; Organik